Atlantic Meridional Overturning Circulation collapse effects on global climate and feedbacks. - Orihuela Pinto, Luis (UNSW, Sydney, 2022)
The importance of the Atlantic Meridional Overturning Circulation (AMOC) on Earth’s climate is primarily via its role in regulating global ocean heat transport. Past climatic states were characterised by a collapsed AMOC and future climate projections suggest that, under a global warming scenario, the AMOC will undergo a weakening that could end in a potential collapse. An AMOC collapse would have major ramifications for Atlantic Ocean heat transport, Arctic sea-ice coverage and regional climate. However, it remains unclear how an AMOC shutdown might impact other regions of the globe. In particular, the AMOC’s connection to tropical climate processes and variability remains unclear and requires further study. Here a global climate model is used to show how an AMOC collapse alters the tropical Pacific atmospheric circulation. This occurs by virtue of the reduced northward oceanic heat transport which leaves an excess of heat in the South Atlantic that triggers atmospheric convection over the area and causes anomalous subsidence in the east Pacific. Subsequently, the Pacific Walker circulation accelerates and cools the tropical Pacific Ocean. Furthermore, the tropical Pacific mean state change due to the AMOC collapse causes a weakening in the atmosphere-ocean coupling locally, which alters the governing El Niño Southern Oscillation (ENSO) feedbacks. Consequently, ENSO events feature a damped growth rate and decreased variability which reduces the frequency of extreme El Niño events and shifts the maximum warming of the majority of El Niño events towards the central Pacific. Finally, an analysis is performed to determine how the tropical Pacific cooling caused by an AMOC collapse could in turn feedback on the AMOC strength. To do this, the resulting Pacific cooling is imposed in a set of model runs and find that the AMOC transport increases. The AMOC strengthening occurs due to an atmospheric teleconnection via Rossby waves moving from the tropical Pacific to the North Atlantic which alter the surface circulation ...